2010
DOI: 10.3892/or_00000718
|View full text |Cite
|
Sign up to set email alerts
|

The angiotensin-converting enzyme 2 in tumor growth and tumor-associated angiogenesis in non-small cell lung cancer

Abstract: Abstract. Angiotensin II (AngII) is a multifunctional bioactive peptide and previous studies have shown that the renin-angiotensin system (RAS) of both host and tumor are important in tumor growth and angiogenesis in lung cancer. Angiotensinconverting enzyme 2 (ACE2) is a newly identified component of RAS, with 42% amino acid homology to ACE. However, the expression and function of ACE2 in non-small cell lung cancer (NSCLC) are still unclear. In the present study, we analyzed ACE2 expression in NSCLC tissue by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 36 publications
0
40
0
Order By: Relevance
“…While the RAS is classically associated with regulation of blood pressure and blood volume, it also plays a role in cancer by inducing angiogenesis, promoting cellular proliferation, and inhibiting apoptosis (19–21). The RAS is dysregulated in malignancy, promoting tumor growth in cancers such as non-small cell lung (22), ovarian (23), pancreatic (24), and prostate (25) cancer, as well as brain tumors such as glioblastoma (GB) (26).…”
Section: Introductionmentioning
confidence: 99%
“…While the RAS is classically associated with regulation of blood pressure and blood volume, it also plays a role in cancer by inducing angiogenesis, promoting cellular proliferation, and inhibiting apoptosis (19–21). The RAS is dysregulated in malignancy, promoting tumor growth in cancers such as non-small cell lung (22), ovarian (23), pancreatic (24), and prostate (25) cancer, as well as brain tumors such as glioblastoma (GB) (26).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on human xenografts in mice clearly indicated that ACE2 inhibited tumor growth by suppressing invasion and angiogenesis in Non-Small Cell Lung Cancer (NSCLC). Remarkably, the same group demonstrated that overexpression of ACE2 promotes the expression of E-cadherin at expenses of mesenchymal markers such as vimentin, and thereby inhibits the epithelial-mesenchymal transition in NSCLC models (Feng et al, 2010;Qian et al, 2013).…”
Section: Ace2 and Other Diseasesmentioning
confidence: 95%
“…ACE2 is a multiform protein (Feng et al, 2010(Feng et al, , 2011. As discussed above (section Structure of ACE2) its C-terminal domain is similar to collectrin, a kidney protein involved in amino acids trafficking and insulin secretion (Kuba et al, 2013).…”
Section: Ace2 and Other Diseasesmentioning
confidence: 99%
“…ACE2 downregulation upon viral infection triggers a cascade of events that contribute to the catastrophic consequences of severe COVID-19 (19). Since ACE2 has been reported to exert multiple anti-tumor effects including inhibition of cancer angiogenesis and metastasis, its downregulation may per se promote tumor progression (20)(21)(22). Second, ACE2 is responsible for the conversion of angiotensin II (AngII) to angiotensin 1-7, a process that plays an important role in the control of inflammation and cardiovascular homeostasis by the renin-angiotensin system (RAS) (23).…”
Section: Role Of Ace2 In Covid-19 and In The Regulation Of Inflammatomentioning
confidence: 99%